Territorial Cohesion of What and Why? The Challenge of Spatial Justice for EU’s Cohesion Policy - Weckroth, Mikko (2020)
Over the past two decades, both academics and policy makers have discussed the meaning of territorial cohesion in the context of the European Union (EU). This debate on the meaning and content of territorial cohesion is becoming increasingly important in a Europe that is facing multiple crises. This article contributes to the literature on EU’s territorial cohesion policies by tracing the ways in which territorial cohesion has been defined, framed and justified as an EU policy. We analyse public speeches made by the acting commissioners for Regional Policy and inquire into the Cohesion Reports from 2004 to 2017 produced by the European Commission. In particular, we interrogate both the meaning of the concept of territorial cohesion and the justifications for pursuing territorial cohesion. We conclude with some critical remarks on the relevance of economic production-based definitions and justifications for territorial cohesion policies. Accordingly, we argue that treating macroeconomic production as an indicator of territorial cohesion harmfully consolidates a narrow understanding of societal wellbeing and development and imposes on all regions a one-dimensional economic scale to indicate their level of development.